Impact of Free Fire Online Games on the Social Behaviorof Class 4 Students of SDN 1 Cipanas Bandung Barat - Wirati, Wirati; Reviyanti, Lysda; Gumilar, Muhammad Ramdan (PT. Riset Press International, 2024)
This research aims to explore the impact of playing the online game Free Fire on the social behavior of grade 4 students at SDN 1 Cipanas, West Bandung. By using descriptive research methods with a qualitative approach, this research revealed that several students experienced an addiction to playing online games which had an impact on various aspects of their behavior. Some of the changes observed include increased emotionality, inability to obey rules, and lack of manners due to the habit of speaking harshly while playing games. This research also found that students more often play games outside the school environment, with the main motivation coming from the excitement and feeling of wanting to win that they get from the game. Although there are several positive impacts such as increasing focus, foreign language skills, and expanding friendship networks, the more dominant negative impacts are seen on students' social behavior, such as irritability, lack of healthy social interactions, and difficulty in managing study time. This research suggests several efforts to overcome this addiction, including limiting playing time, finding new hobbies, and placing gaming devices outside the bedroom.